Español - Gutiérrez Rojas, Janeth Rosario (2021)
The purpose is to analyze the academic contributions to the development of emotional intelligence in adolescents. The methodology employed was a descriptive systematic review, using the PRISMA Declaration guide, the search for information was carried out in the online databases Scopus, ProQuest, Concytec and EBSCO. The review took into account emotional self-regulation, protective factors, emotional competencies and the appropriate context for their enhancement. The results were the analysis of 13 rigorous scientific publications, of which 4 were Scopus, 4 ProQuest, 3 Concytec, 2 EBSCO and 12 were of correlational design and 1 of quasi-experimental design. The conclusions showed that emotional intelligence refers to the psychological abilities and capacities that involve affections, talents, verification and transformation of one's own and other people's emotions; that individuals have not been concerned about developing them in an optimal way, giving importance only to the rational part and neglecting the emotional part. Keywords: Socio-emotional; skills; anxiety; personality; culture.